Enhanced desalination performance of thin-film composite forward osmosis membranes through multilayer graphene oxide-modified mixed-matrix polyethersulfone substrates - Almansouri, Hamza E.; Edokali, Mohamed; Mazrul Nizam, Abu Seman; Ntone, Ellora Priscille Ndia; Che Ku Mohammad Faizal, Che Ku Yahya; Abdul Wahab, Mohammad (Springer, 2025)
Forward osmosis (FO) has emerged as an energy-efficient, membrane-based desalination technology; however, challenges related to internal concentration polarization (ICP) and fouling persist. This study investigates the enhancement of thin-film composite (TFC) FO membranes through the incorporation of multilayer graphene oxide (GO)-modified polyethersulfone (PES) substrates to optimize water flux, selectivity, and antifouling properties. Various GO loadings were systematically analyzed to determine the optimal concentration for membrane performance. Membranes were characterized using ATR-FTIR, XPS, WCA, FE-SEM, and AFM, while performance evaluations focused on water flux, reverse solute flux, and antifouling capabilities under laboratory-scale FO conditions. Results showed that a 0.1 wt.% GO loading significantly improved hydrophilicity and porosity while reducing structural resistance, leading to increased water flux (5.12 LMH), decreased reverse solute flux (25.3 gMH), and lower specific reverse solute flux (4.95 g/L), surpassing the performance of the control membrane. Additionally, the modified PES support layer exhibited enhanced antifouling properties by minimizing fouling through increased surface smoothness and electrostatic repulsion, thus maintaining membrane stability during prolonged operation, contributing to a lower total flux decline rate (35%) and a higher flux recovery rate (97%). These findings highlight an improved balance between desalination efficiency and antifouling performance in GO-modified membranes, establishing a scalable pathway toward high-performance FO membranes for sustainable water desalination applications.